PENGUKURAN RISIKO OPERASIONAL AGROINDUSTRI MINYAK KAYU PUTIH KUPANG MOJOKERTO DENGAN METODE FMEA - Devani, Livia Marcella; Mubarokah, Mubarokah; Rozci, Fatchur (Jurnal Hutan Tropis, 2024)
Kupang Mojokerto Eucalyptus Oil Agroindustry is a modern industry engaged in distilling eucalyptus leaves into eucalyptus oil products. This study aims to describe the level of operational risk measures that have the potential to occur in the Kupang Mojokerto Eucalyptus Oil Agroindustry. The method used in measuring the level of potential operational risk is Failure Mode and Effect Analysis (FMEA) which serves to identify and analyze the occurrence of potential operational risks so that companies can carry out appropriate risk control based on the risk priority number (RPN) value with a high criticality category. The results showed that the types of operational risks in the high criticality category include not maximizing evaporation with RPN 360, receiving raw materials in the rainy season in wet and budding conditions with RPN 348, dependence on certain technologies with RPN 346, and weather conditions with high rainfall intensity with RPN 336. Measurement of the level of operational risk is carried out so that the company can control and anticipate the occurrence of risks in operational activities.